Adaptive analysis of infinite beams dynamics problems using the periodic configuration update method in the time domain. (15th November 2017) - Mezeh, Reda; Sadek, Marwan; Hage Chehade, Fadi; Shahrour, Isam
Summary: This paper proposes a new approach for the assessment of the dynamic response of continuously supported infinite beams under high‐speed moving loads. A change in the representation of equations of motion in the dynamics of discrete structures is proposed to obtain an improved accuracy of the numerical integration in the time domain. The proposed numerical method called the "periodic configuration update" or "PCU method" is applied to solve the problem of a vertical moving harmonic load on an infinite classical Euler‐Bernoulli beam resting on a continuous viscoelastic foundation. This study shows the superiority of the proposed method in comparison with other methods presented in the literature that suffer from the material time derivative, i.e., convective terms, that arises from the Galilean transformation. To confront this numerical problem, the PCU method retains the principle of the spatial follow of loads while zeroing the relative velocity with the traversed beam via a step‐by‐step adaptive integration of the equation of structural dynamics. The dynamic load is modeled with high theoretical velocities that can reach the critical velocity of the studied beam with different angular frequencies belonging to moderate frequency range. A parametric study is carried out to analyze the influence of key parameters on the convergence. The obtained results show a high efficiency of the PCU method for solving these types of problems relative to the dynamics of high speed trains/tracks.